1976
DOI: 10.1042/bj1550217
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and properties of α-D-mannosidase from human kidney

Abstract: Alpha-D-Mannosidase activity exists in three forms that can be separated by DEAE-cellulose chromatography, alpha-D-Mannosidase was isolated from human kidney in a homogeneous state, and was purified 2100-fold, with p-nitrophenyl alpha-D-mannoside as substrate. The purified alpha-D-mannosidase was practically free from all other glycosidases tested. The Km of the synthetic substrate with the enzyme was 1 X 10(-3) M and the pH optimum 4.5. It was inhibited by heavy metals, sodium dodecyl sulphate, urea and compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The multiple isozymes are often related to the involvement of two or more genetically determined nonidentical subunits for consti tution of an enzyme. Several authors have suggested that acidic a-mannosidase is a dimer [12,17]. However, no clear single sub unit band was evident on their SDS electro phoresis gels.…”
Section: Resultsmentioning
confidence: 99%
“…The multiple isozymes are often related to the involvement of two or more genetically determined nonidentical subunits for consti tution of an enzyme. Several authors have suggested that acidic a-mannosidase is a dimer [12,17]. However, no clear single sub unit band was evident on their SDS electro phoresis gels.…”
Section: Resultsmentioning
confidence: 99%
“…The collagen gel microstructure was approximated by a collection of 3D fiber networks that have been shown to resemble the structure and heterogeneity observed experimentally [1,2]. In this study, each element in the FE mesh was randomly assigned a 3D fiber network containing on average 323 ± 26 cross-linked fibers.…”
Section: Microscale Network and Cell Compactionmentioning
confidence: 99%
“…Recently, it has been demonstrated that in addition to soluble biochemical factors, the properties of the surrounding extracellular matrix (ECM) and the local mechanical environment profoundly influence cell behavior [1][2][3][4][5]. The mechanical environment is controlled in part by the composition and stiffness of the local ECM and by the manner in which physical forces applied at the tissue-level propagate down to the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…The activity can be restored immediately by the addition of excess zinc. Thus, the loss of Zn2' during purification may in some cases account for the poor recoveries [e.g., see (521)l and differences in purity and in incubation conditions may explain controversial results on ZnZ + requirement of the enzyme (519,(522)(523)(524)526,527,541). In the presence of 1-mM Zn" , a-mannosidase is stable at 65"C, pH 6.0 for at least 1 h (537).…”
Section: G A-mannosidasementioning
confidence: 99%